A Review of Goal-Directed Cardiopulmonary Bypass Management in Pediatric Cardiac Surgery. Issue 5 (September 2018) - Medikonda, Ravi; Ong, Chin Siang; Wadia, Rajeev; Goswami, Dheeraj; Schwartz, Jamie; Wolff, Larry; Hibino, Narutoshi; Vricella, Luca; Barodka, Viachaslau; Steppan, Jochen
Cardiopulmonary bypass perfusion management significantly affects postoperative outcomes. In recent years, the principles of goal-directed therapy have been applied to the field of cardiothoracic surgery to improve patient outcomes. Goal-directed therapy involves continuous peri- and postoperative monitoring of vital clinical parameters to tailor perfusion to each patient's specific needs. Closely measured parameters include fibrinogen, platelet count, lactate, venous oxygen saturation, central venous oxygen saturation, mean arterial pressure, perfusion flow rate, and perfusion pulsatility. These parameters have been shown to influence postoperative fresh frozen plasma transfusion rate, coagulation state, end-organ perfusion, and mortality. In this review, we discuss the recent paradigm shift in pediatric perfusion management toward goal-directed perfusion.